Students' commuting pattern from the viewpoint of environmentalism: comparing Australia with China. Issue 1 (22nd February 2019) - Soltani, Ali; Allan, Andrew; Nguyen, Ha Anh; Berry, Stephen
Abstract : Purpose: This paper aims to clarify the differences between students' travel behaviours in Australia and China and the association between students' environmental attitudes and their travel behaviours in both countries. Design/methodology/approach: The paper extensively reviewed most of existing literature work on commuting patterns of higher education students with referring to different studies around the world and then used it to build a theoretical framework and conceptual model to relate the travel patterns of students to built environment, personal demographics and environmental knowledge/consideration. An online survey was used with 230 students at Mawson Lakes campus of University of South Australia and Beiyangyuan campus of Tianjin University (China). Statistical tests (i.e. mean test, one-way analysis of variance, factor analysis) were used to analyse the data. Findings: The study reveals that a high dependence on private vehicles amongst students at the Mawson Lakes campus, whilst a more environmentally sustainable modal choice dominated at the Beiyangyuan campus. Those who studied at Mawson Lakes campus tended to have stronger involvement in environmental activities than their counterparts at Beiyangyuan campus, which presented a clear association between environmental awareness and the travel behaviours of the sampled students. Research limitations/implications: The study focussed on two respective campuses of both universities in Australia and China. Future work could be expanded with students at all campuses of two universities. Practical implications: The study affirmed the value of nurturing environmental awareness for students in both universities to encourage more environmentally sustainable travel behaviours amongst students. The paper provides policy recommendations such as establishing infrastructure, and facilities for new stream of mobility included sharing bike schemes, which would be very practical due to flexibility and cost effectiveness within University campuses. The paper attempted to transfer lessons from Chinese bike friendly society to Adelaide's car dominated campus. Originality/value: This study brings remarkable contributions as comparing university students' travel behaviours in two different nations. It is the first one in Australia, which links the environmental concerns among university students with their travel behaviours. The paper was successful in getting the gap between theory and practice filled to some extent. The paper has a capability to be used as an evidence-base work in the area of sustainability education.